Endonasal flap suture-dacryocystorhinostomy (eFS-DCR): a new surgical technique for nasolacrimal duct obstruction (NLDO). (February 2014) - Tachino, Hirohiko; Fujisaka, Michiro; Fuchizawa, Chiharu; Tsubota, Masahito; Takakura, Hiromasa; Ishida, Masayuki; Hayashi, Atsushi; Shojaku, Hideo
Abstract Conclusion: Endonasal flap suture-dacryocystorhinostomy (eFS- DCR) is a new and valuable technique for the treatment of nasolacrimal duct obstruction (NLDO). This technique could improve the success rate of endonasal DCR in comparison to external DCR. Objective: The standard procedure for NLDO is DCR. DCR can be performed via either an external or endonasal approach. External DCR is now regarded as the gold standard in the treatment of NLDO because of its higher success rate. However, we report a new endonasal surgical technique, eFS-DCR, and assess its efficacy by comparison with the standard endonasal DCR. Methods: We prospectively investigated a series of 62 consecutive patients with NLDO undergoing endonasal DCR. There were two surgical intervention groups: group 1 (24 patients, 28 sites) undergoing endonasal DCR without eFS; and group 2 (38 patients, 47 sites) undergoing eFS-DCR. Study end points were success rate, the ostium diameter (OD) of the lacrimal sac after DCR, and the duration of stent placement. We compared the two groups on these three points. Results: The success rate was 78.6% (22 of 28 sites) for group 1 (DCR without eFS) and 97.9% (46 of 47 sites) for group 2 (eFS-DCR). The ostium size in patients in group 2 was larger than that in group 1. The median time for the duration of stent placement was 42.5 days for group 1 and 31.5 days for group 2. There was a statistical difference (p < 0.01) in all these parameters between the two groups.